ATRT-03. MALIGNANT RHABDOID TUMORS ORIGINATING WITHIN AND OUTSIDE THE CENTRAL NERVOUS SYSTEM ARE CLINICALLY AND MOLECULARLY HETEROGENEOUS. Issue 2 (22nd June 2018) - Pinto, Emilia; Hamideh, Dima; Bahrami, Armita; Orr, Brent; Lin, Tong; Pounds, Stanley; Zambetti, Gerard; Pappo, Alberto; Agnihotri, Sameer; Gajjar, Amar; Broniscer, Alberto
Abstract: Multifocal synchronous/metachronous ATRTs and extra-CNS MRTs are rare. We reviewed clinicoradiologic characteristics of affected patients. Genotyping and copy number abnormality (CNA) analysis in SMARCB1 were performed in germline and tumor samples. Tumor samples underwent DNA methylation and CNA analysis. Median age at diagnosis (n=21 patients) was 0.6 years. Two-thirds of patients had synchronous tumors. Although kidney tumors predominated, at least 30% of cases lacked renal involvement. Histopathologic review confirmed MRTs in all cases and INI1 expression loss in all tumors tested. Fourteen (78%) of 18 patients tested had heterozygous germline SMARCB1 abnormalities. Mono and biallelic SMARCB1 abnormalities were confirmed in at least 50% and 80% of tumors, respectively. Unsupervised hierarchical clustering analysis of DNA methylation in 27 tumors and comparison to 150 reference ATRTs classified 14 multifocal ATRTs as SHH (64%), tyrosinase (21%), and MYC (14%). The MYC subgroup accounted for 85% of 13 extra-CNS MRTs. Of 16 paired ATRTs and extra-CNS MRTs, 7 of 8 patients had tumors with different patterns of DNA methylation and/or CNAs suggestive of non-clonal origin. CNS and extra-CNS tumors had an identical SMARCB1 amplification (n=1) or similar DNA methylation pattern (n=1) suggestive of clonal origin. All patients died of tumor progression. The clinical and molecular characteristics of multifocal ATRTs and extra-CNS MRTs are heterogeneous with most patients harboring a cancer predisposition. Although independent tumor origin was confirmed in most cases, metastatic spread was also documented. The recognition of their distinct molecular characteristics is critical in selecting new biologic therapies against these deadly cancers.